Diagnostic Analysis of Electrolytes (NA+, k+, CL-, MG+2 and PO-34) in Cadaveric Synovial Fluid from Knee Joint to Estimate Postmortem Interval - Aatiqa Abbas, Arooj Farooq, Muhammad Ali Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Accurate determination of Time since death (TSD) has always been a challenge to forensic pathologists. Due to non-precise results using physical methods to estimate time of death, focus has been shifted to biochemical methods using body fluids. Previously, body fluids like cerebrospinal fluid (CSF) and vitreous humour have been used to determine postmortem interval (PMI), but in cases of head and ocular injuries respectively, they can be rendered useless. Synovial fluid is a well-preserved, compartmentalized fluid and hence, can be used to estimate PMI. The aim of this study was to determine death interval based on synovial fluid electrolytes levels (Na+, K+, Cl-, Mg+2, PO-34) and to assess its reliability for future studies. Study design: It was a correlational study. Study settings: The research was conducted at department of Forensic Medicine King Edward Medical University, Mayo Hospital Lahore, from August 2018 to August 2019. Methodology: PMI was regressed on synovial fluid electrolytes and regression formulae were formulated. Significant positive correlation was found between time since death and K+ ion concentration using regression formula. Results: However, there was negative relationship between PMI and Na+ and no significant relationship was found between TSD and Cl-, Mg+2 and PO-34 concentrations. The regression model of K+ gave a 97.9% accuracy and a correlation coefficient of 0.978 which showed the model using K+ values in synovial fluid is the most accurate one. Conclusion: The concentration of potassium ions increases with increasing time of death whereas, that of sodium decreases with increasing PMI. However, magnesium, chloride and phosphate concentrations remain unchanged with time interval.